Microstructural and mechanical properties of 17-4PH stainless steel fabricated via material extrusion 3D printing - Cao, Dang Long; Nguyen, Van Cuong; Thi, Van Nga Tran (Teknomekanik, 2025)
This study investigates the microstructural and mechanical properties of metal 3D printing products fabricated using material extrusion technology. It focuses on the critical post-processing stages: printing, washing, and sintering. A Markforged 3D printing system and 17-4 PH stainless steel material were utilized to assess the effect of printing orientation and sintering conditions on microstructural and mechanical properties of the final product. The results demonstrate that printing orientation and sintering conditions critically govern the microstructural and mechanical properties of the final product. During sintering, the microstructure undergoes significant phase transformation and densification, while micropores and shrinkage voids emerge due to capillary stresses during binder removal. Furthermore, the mechanical properties are significantly influenced by the combined effects of printing orientation and sintering conditions. Optimizing deposition parameters (printing orientations and sintering conditions) substantially enhances the mechanical performance of the final printed product.